Nursing ethics and professional responsibility in advanced practice - Grace, Pamela June; Uveges, Melissa K. (Melissa Kurtz) (Burlington, Massachusetts Jones & Bartlett Learning, 2023)
"This book focuses in an in-depth way on the particular problems faced by nurses in various advanced practice roles across the life-span and in front-line care. It is comprehensive textbook broken out into three sections: philosophical foundation, ethics, and specialty focus"--
Philosophical Foundations of Applied and Professional Ethics / Pamela Grace -- Nursing Ethics / Pamela Grace -- Advanced Practice Nursing : The Nurse-Patient Relationship and General Ethical Concerns / Aimee Milliken, Eileen Amari-Vaught, & Pamela J. Grace -- Professional Responsibility, Social Justice, Human Rights, and Injustice / Pamela J. Grace & John C. Welch -- Ethical Leadership by Advanced Practice Nurses / Pamela J. Grace & Nan Gaylord -- Research Ethics : Advanced Practice Roles and Responsibilities / Pamela Grace & Melissa Uveges -- Nursing Ethics and Advanced Practice : Neonatal Issues / Peggy Doyle Settle -- Nursing Ethics and Advanced Practice : Children and Adolescents / Nan Gaylord -- Nursing Ethics and Advanced Practice : Women's Health/Gender-Related Care / Allyssa L. Harris, Pamela J. Grace, Melissa K. Uveges -- Nursing Ethics and Advanced Practice : Caring for Adults and Older Adults / Pamela J. Grace and Jane Flanagan -- Nursing Ethics and Advanced Practice : Psychiatric and Mental Health Issues / Pamela J. Grace, Elizabeth Lessman, and Danny G. Willis -- Nursing Ethics and Advanced Practice in the Anesthesia and Perioperative Period / Allan C. Thomas, Gregory Sheedy and Pamela J. Grace -- Nursing Ethics and Advanced Practice : Palliative and End of Life Care Across the Lifespan / Stewart M. Bond, Jane E. Castle, Melissa K. Uveges and Pamela J. Grace.
Includes bibliographical references and index.
Keywords: Advanced Practice Nursing -- ethics; Ethics, Nursing